Caracterização e reciclagem eletroquímica dos cátodos exauridos das baterias de íon-Li de telefones celulares - Garcia, Eric Marsalha (2008)
In this work, a method for electrochemical recycling of cobalt present in cathode of the spent Li-ion batteries has been proposed. The cathodes composition characterized by X-ray diffraction is: LiCoO2, C, Al and Co3O4. With the help of Electrochemistry Quartz Crystal Microbalance (EQCM) investigated the cobalt eletrodeposition mechanism. Was observed that the cobalt electrodeposition occurs by direct mechanism at pH = 5.40. The cobalt eletrodeposition mechanism in pH = 2.70 depends on the applied technique. In potentiodinamic conditions the cobalt electrodepossition occurs by the mechanism of adsorbed hydrogen. In potentiostatic conditions, it verified that the cobalt reduction occurs simultaneously by direct reduction and adsorbed hydrogen mechanism. The cobalt electrodeposition on the Al is strong influenced by pH solution. A maximum charge efficiency to potentiostatic cobalt electrodeposition on Al is obtained in potential equal to -1.00 V so much for pH = 5.40 as for 2.70. Maximum charge efficiency is obtained at pH = 5.40 is equal to 96%. The potentiostatic electrodeposition of cobalt follows the progressive nucleation model in pH = 5.40 and is best described by instantaneous nucleation model in pH = 2.70. The morphology and structure were characterized with help of the Scanning Electronic Microscopy (SEM) and X-Ray Diffraction (DRX) and were correlated with the growth mechanism of the cobalt electrodeposition. The mechanism 3D occurs preferentially in pH = 5.40 and 2D in pH = 2.70 for charge density of 10.0 Ccm-2. The cobalt electrodeposits growth is better described by a simultaneous mechanism 2D and 3D with the charge density increase for 50.0 C cm-2. The charge density of the cobalt electrodissolution depends on the deposit structure and morphology.